2019
DOI: 10.31234/osf.io/c7456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy flows in gesture-speech physics: Exploratory findings and pre-registration of confirmatory analysis

Abstract: A well-known phenomenon of multimodal language is the synchronous coupling of prosodic contours in speech with salient kinematic changes in co-speech hand-gesture motions. Invariably, such coupling has been rendered by psychologists to require a dedicated neural-cognitive mechanism preplanning speech and gesture trajectories. Recently, in a continuous vocalization task, it was found that acoustic peaks unintentionally appear in vocalizations when gesture motions reach peaks in physical impetus, suggesting a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The current confirmatory study was preceded by preliminary findings (Pouw, Harrison, Esteve-Gibert, & Dixon, 2019) obtained from an exploratory dataset which formed the basis of the pre-registration of the current analysis (https://osf.io/x7zdc/). In this exploratory study, we found promising results which we test here in replicatory fashion.…”
Section: A Current Studymentioning
confidence: 99%
“…The current confirmatory study was preceded by preliminary findings (Pouw, Harrison, Esteve-Gibert, & Dixon, 2019) obtained from an exploratory dataset which formed the basis of the pre-registration of the current analysis (https://osf.io/x7zdc/). In this exploratory study, we found promising results which we test here in replicatory fashion.…”
Section: A Current Studymentioning
confidence: 99%
“…To address the first issue, there is evidence that respiratory-vocalic aspects of speech such as the fundamental frequency and intensity are directly modulated by physical impulses that are produced by beat-like upper limb movements [3][4][5][6]. This modulation is attributed to upper limb movements recruiting a wider ensemble of posture-maintaining muscles around the trunk which are implicated with control of expiration [7][8][9] and thus vocalic aspects of speech [5,10]. What this means is that there is a causally dependent biophysical relationship between vocalic aspects of speech and upper limb movements.…”
mentioning
confidence: 99%